Strong Notch activation hinders bevacizumab efficacy in advanced colorectal cancer. (December 2015) - Negri, Francesca V; Crafa, Pellegrino; Pedrazzi, Giuseppe; Bozzetti, Cecilia; Lagrasta, Costanza; Gardini, Giorgio; Tamagnini, Ione; Bisagni, Alessandra; Azzoni, Cinzia; Bottarelli, Lorena; Graiani, Gallia; Romano, Ida; et al.
Aim: To assess the role of Notch activation in predicting bevacizumab efficacy in colorectal cancer (CRC).Materials & methods: Notch activation was evaluated by immunohistochemistry (IHC) on 65 CRC enrolled within randomized clinical trials assessing first-line bevacizumab-based chemotherapy and on 21 CRC treated with chemotherapy alone.Results: Strong Notch (IHC 3+) activation was negatively associated with response (18 vs 62% in low Notch cases [IHC 0, 1, 2+]; p = 0.016), progression-free survival (4.9 vs 12.1 months; p = 0.002) and overall survival (19.3 vs 30.4 months; p = 0.039). No correlation was found between Notch activation and clinical outcome in CRC treated with chemotherapy alone.Conclusion: A potential role of Notch activation in the antitumor activity of bevacizumab could be hypothesized.